Instant CMQT stabilization coupled UHPLC-MS/MS for the quantification of reduced and total forms of cysteine, homocysteine, and glutathione in blood plasma - Yongyin Zhou; Haizhu Tan; Yingtong Chen; Hongjun Luo; Hui Li; Wenhong Luo; Yingxiu Xiao; Zhexuan Lin (Analytica Chimica Acta, 2026)

Reprogramming oily water separation with Janus membranes: From asymmetric fabrication to engineering perspectives - Mingyi Ying; Bisheng Li; Jiaheng Teng; Xiang Cai; Cheng Chen; Leihong Zhao; Hongjun Lin (Journal of Environmental Chemical Engineering, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Interfacial energy homogenization enables β-phase transition and high piezoactivity in MOF/PVDF membrane for sustainable pollutant degradation - Zi Yang; Miaomiao Tian; Cheng Chen; Zhiyu Zhao; Libo Zhao; Jiujing Xu; Wei Yu; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Biofilm ecology in wastewater treatment systems: From microscale ecological insights to macroscale process optimization - Shasha Yuan; Pei Li; Ziyang Xie; Zili Zhou; Zhongbo Zhou; Chao Wang; Die Ling Zhao; Fangang Meng; Hongjun Lin (Critical Reviews in Environmental Science and Technology, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

Adsorption and ligand-to-metal charge transfer (LMCT)-driven photodegradation of PFOA/PFOS by iron-based materials: Mechanistic insights and environmental risk analysis - Tao Jian; Bisheng Li; Cheng Chen; Leihong Zhao; Xiang Cai; Hongjun Lin; Xiaohong Guan (Critical Reviews in Environmental Science and Technology, 2026)

Flexible MOF nanosheet based membranes for high-flux antifouling oil/water separation and reverse cross-flow cleaning - Ting Gong; Jizheng Shang; Hongyuan Zhu; Yifan Liu; Hang Jiang; Shasha Yuan; Liguo Shen; Die Ling Zhao; Hongjun Lin (Journal of Hazardous Materials, 2026)

Unregulated delayed emissions dominate ultrafine particles from modern diesel vehicles - Fuyang Zhang; Jianfei Peng; Peiji Liu; Yajun Wu; Jinsheng Zhang; Jiayuan Liu; Kexin Liu; Bin Sun; Qijun Zhang; Lin Wu; Ning Yang; Miao Tang; et al. (Journal of Hazardous Materials, 2026)

Spatiotemporal differences in traffic efficiency and CO2 emissions across day types: A city-level data-driven analysis of cooperative vehicle-infrastructure systems - Bin Sun; Haoyu Xu; Zhaolang Wu; Qijun Zhang; Lin Wu; Yan Liu; Yanan Mi; Hongjun Mao (Journal of Environmental Management, 2026)

Opening the window to the solar-driven world of MXenes: Mechanisms, synergistic strategies, and emerging applications for sustainable environmental purification - Xiao Zhang; Yingzi Du; Wenzhe Yu; Mingzhu Zhou; Xiang Cai; Leihong Zhao; Hongjun Lin; Bisheng Li (Critical Reviews in Environmental Science and Technology, 2026)

Influence of aspect ratio on the dynamic performance of suction caisson supported wind turbines: insights from wind tunnel tests - Yixiao Chen; Kun Lin; Annan Zhou; Hongjun Liu (Ocean Engineering, 2026)

Health risks from PM2.5-bound heavy metals from religious burning activities on the plateau - Zhaoquan Yu; Lei Yang; Jiawei Yin; Haomiao Niu; Zhou Xu; Hao Qin; Liuyang Guo; Yan Liu; Lin Wu; Qijun Zhang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Electric-field-modulated charge transfer enables efficient molecular oxygen activation on Bi2MoO6/NaNbO3 type-II heterojunction for broad-spectrum antibiotic degradation - Zhuoran Lin; Mingzhu Zhou; Zeyu Zhou; Xiaoyan Tan; Bisheng Li; Renjie Li; Leihong Zhao; Hongjun Lin (Journal of Environmental Chemical Engineering, 2026)

Synergistic integration of NiFe-MOF and carbon quantum dots for multifunctional nanofiltration membranes with high permeability and photocatalytic self-cleaning - Zhao Chen; Yifan Liu; Hongyuan Zhu; Haiyi Jin; Shasha Yuan; Die Ling Zhao; Hongjun Lin (Desalination, 2026)

Integrating adsorptive filtration and visible-light peroxymonosulfate activation in a Fe3O4@ZIF-67@polydopamine/PTFE membrane for one-pass treating copper–tetracycline mixed wastewater - Zengjian Zhao; Tao Jian; Wenzhe Yu; Jiaheng Teng; Leihong Zhao; Qian Lei; Hongjun Lin (Chemical Engineering Journal, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Evaluating the effectiveness of tightened emission standards in reducing real-world vehicle emissions: Evidence from on-road testing and inventory analysis - Lei Yang; Zhaoquan Yu; Haomiao Niu; Hao Qin; Jiawei Yin; Zhou Xu; Yan Liu; Lin Wu; Jianfei Peng; Hongjun Mao; Qijun Zhang (Journal of Cleaner Production, 2026)

Decoding enhanced oily wastewater purification and photocatalytic self-cleaning performance of magnetic field-strategized composite membranes with surface-localized CoFe2O4@PDA - Yifan Liu; Hang Jiang; Hongyuan Zhu; Zhenyu Guo; Shasha Yuan; Liguo Shen; Die Ling Zhao; Hongjun Lin (Journal of Hazardous Materials, 2026)

Dual-function tara gum-based antiscalant with efficient antiscaling and antibacterial activity: Performance and molecular simulation investigation - Liping Xiong; Wei Yu; Xinyi Lu; Zhiyu Zhao; Cheng Chen; Renjie Li; Guanhua Jin; Leihong Zhao; Hongjun Lin; Liguo Shen (Journal of Environmental Chemical Engineering, 2026)

Dynamic performance of suction caisson supported offshore wind turbines under different operational conditions - Kun Lin; Yixiao Chen; Annan Zhou; Hongjun Liu (Engineering Structures, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Microstructure-engineered NiFe-LDH composite membranes integrating high flux with visible-light-driven self-regeneration for sustainable treatment of complex oily water - Hongyuan Zhu; Yifan Liu; Shasha Yuan; Liguo Shen; Hongjun Lin; Sui Zhang; Die Ling Zhao (Desalination, 2026)

Novel insight into combined heavy metal and polysaccharide fouling in forward osmosis: Role of water state evolution mediated by reverse solute diffusion - Xiujia You; Hanmin Zhang; Hongjun Lin (Desalination, 2026)

Spatiotemporal patterns of super-emitting diesel vehicles: A scalable remote sensing framework for urban emission hotspot mitigation - Junxia Gao; Yan Liu; Ning Yang; Zeping Cao; Jing Zhao; Lin Wu; Wentian Xu; Binfeng Yan; Zhengyu Jia; Hongjun Mao (Atmospheric Pollution Research, 2026)

Real-world key-process emission factors optimized environmental impact from passenger car tires’ PM2.5 and typical chemicals throughout lifecycle - Tiange Fang; Lei Sheng; Qiang Zeng; Guang Yang; Jinsheng Zhang; Wendi Wei; Jianfei Peng; Lin Wu; Ting Wang; Jing Zhang; Hongjun Mao (Journal of Hazardous Materials, 2026)

Low-intensity ultrasound enhances lipid biosynthesis in algae-bacteria consortia and improves symbiotic system stability in wastewater treatment - Yuwei Zhang; Yilin Zhou; Hongjun Lin; Leihong Zhao; Mingyi Ying; Meijia Zhang (Journal of Environmental Chemical Engineering, 2026)

Triatomic-doped MXene based catalyst with sodium alginate encapsulation their molecular and DFT calculation study for efficient photocatalytic removal of disinfected by-product from drinking water - Saleem Raza; Ata Ur Rehman; Zhiyu Zhao; Hua Li; Cheng Chen; Wei Yu; Ying Liu; Yanchao Xu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Linear diacyl chloride enables polyamide nanofiltration membranes with balanced permeability and selectivity for efficient dye desalination - Jiujing Xu; Cheng Chen; Zhiyu Zhao; Leihong Zhao; Wei Yu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Boron nitride nanosheets via arginine-assisted embedded with phosphomolybdic acid as pesticide carriers for visualization in pest control - Li Hao; Minyan Zhou; Jialin Zeng; Jiechun Lin; Lan Hua; Ziting Yin; Mei Guan; Qiangcheng Zheng; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

Open the door to the new world of singlet oxygen in the peracetic acid system: Generation and identification - Rui Liu; Wen Lu; Yuting Liu; Mingzhu Zhou; Bisheng Li; Hongjun Lin; Jiaheng Teng; Liguo Shen; Xiaohong Guan; Leihong Zhao (Water Research, 2026)

Multiscale thermodynamic insights into membrane fouling control by biochar-activated peroxymonosulfate pretreatment: Synergy of oxidation and adsorption - Mingjing Xie; Wenfa Yang; Xiaoni Zhou; Biyan Wang; Jiaqi Liu; Xiao Xu; Liguo Shen; Hanmin Zhang; Meijia Zhang; Wei Yu; Jiaheng Teng; Hongjun Lin; et al. (Water Research, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Electroactivated cobalt-cobalt Prussian blue analog composite membrane for rapid persulfate-driven antibiotic degradation and fouling mitigation - Xiaoyue Yao; Hao Wang; Jingjing Liu; Yu Wang; Xuewen Tang; Hongjun Lin; Leihong Zhao; Bisheng Li; Renjie Li (Chemical Engineering Journal, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

Hydrogen-bonded organic framework enables ultrathin polyamide membrane for efficient endocrine disrupting compounds removal - Jiujing Xu; Xueyu Wang; Cheng Chen; Rukang Jiang; Boya Wang; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin; Banglin Chen (Chemical Engineering Journal, 2026)

A novel magnetically induced Co@NC-modified electrochemical membrane for continuous peroxymonosulfate activation: achieving ultrafast and cost-effective purification with elucidation of mechanism and application potential - Xiaoyue Yao; Renjie Li; Liguo Shen; Leihong Zhao; Hongjun Lin (Water Research, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Experimental investigation of the hydrodynamic response of a cantilevered gas-conveying flexible tube - Hongjun Zhu; Peng Liu; Yue Gao; Lin Ding; Tongming Zhou (Ocean Engineering, 2025)

Altitude-driven vehicle particle emission surges: Insights from chemical analysis and machine learning - Zhiwen Jiang; Haomiao Niu; Yujie Wu; Lin Wu; Zhou Xu; Hao Qin; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Enhanced built-in electric field and strong interfacial electronic coupling in 2D/2D BiO2-x/Ti3C2 Schottky heterojunction boost exciton dissociation for sustainable molecular oxygen activation toward 100 % singlet oxygen generation - Chongyang Yang; Song Tian; Yanyan Liu; Liguo Shen; Cheng Chen; Yanchao Xu; Leihong Zhao; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Particle number emissions on mountainous roads: machine learning insights from on-road testing - Zhiwen Jiang; Yujie Wu; Lin Wu; Haomiao Niu; Wei Feng; Wentian Xu; Jiawei Yin; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Environmental Research, 2025)

Thiol-ene click synthesis of a novel alginate-derived adsorbent: Synergistic adsorption and mechanistic investigation of dye and antibiotic - Xinyi Lu; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Guanhua Jin; Leihong Zhao; Saleem Raza; Liguo Shen (Desalination, 2025)

Molecular insights in outstanding performance of Ca2+ bridging MXene/Sodium alginate composite membranes - Hua Li; Hongjun Lin; Saleem Raza; Zhiyu Zhao; Siyuan Chen; Yue Wang; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Water Research, 2025)

Advanced membrane technology for per- and polyfluoroalkyl substances removal: Innovations in membrane materials and hybrid systems - Wei Yu; Jiaheng Teng; Xiang Cai; Liguo Shen; Genying Yu; Bisheng Li; Leihong Zhao; Hongjun Lin (Journal of Environmental Management, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Magnetic-field-assisted fabrication of Fe3O4-enhanced thin-film nanocomposite polyamide nanofiltration membranes with enhanced separation performance - Congcong Zhou; Zhihao Chen; Jingfen Yuan; Yang Jiao; Hongjun Lin; Yanchao Xu (Desalination, 2025)

Double cross-linking architectonics membranes for high-efficiency oil-water separation and the mechanistic investigation - Yue Wang; Hongjun Lin; Siyuan Chen; Hua Li; Zhiyu Zhao; Qianqian Zeng; Cheng Chen; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2025)

Magnesium-enriched biochar as a multifunctional carrier: unlocking productivity and stability in the algal-bacterial symbiosis system - Xiu Zhang; Xiang Cai; Xin Hu; Chenlu Zong; Hongjun Lin; Liguo Shen; Jiaheng Teng; Bisheng Li; Leihong Zhao; Meijia Zhang (Chemical Engineering Journal, 2025)

Magnetically directed interfacial polyamerization of Fe3O4@CdS@CQDs-embedded polyamide nanofiltration membranes with enhanced separation and photocatalytic self-cleaning performance - Erqiao Chen; Zhihao Chen; Zhongting Liu; Mingzhu Zhou; Bisheng Li; Renjie Li; Liguo Shen; Yang Jiao; Hongjun Lin; Yanchao Xu (Chemical Engineering Journal, 2025)

Unrecognized emissions and health risks of intermediate-volatility organic compounds in vehicle cabins: Insights from a nontargeted analytical approach - Haoning Chang; Yajun Wu; Jing Zhang; Dianjia Liu; Yao Zeng; Pengfei Song; Jinsheng Zhang; Yan Liu; Lin Wu; Ting Wang; Hongjun Mao; Jianfei Peng; et al. (Journal of Hazardous Materials, 2025)

3D-printed super-wetting membranes with in situ grown MOF for efficient oil-water separation - Siyuan Chen; Zhiyu Zhao; Cheng Chen; Wei Yu; Xinchun Lu; Yue Wang; Hua Li; Qianqian Zeng; Hongjun Lin; Leihong Zhao; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2025)

Biotransformation and toxicity attenuation of 2,6-Dichlorobenzoquinone in simulated human gastrointestinal conditions: Insights from a systematic in vitro study - Lili Zheng; Guolong Chen; Kuangtao Fu; Zhen Wang; Xinyue Yuan; Hongjie Sun; Wenjing Deng; Zeqiong Xu; Hongjun Lin; Huachang Hong (Journal of Hazardous Materials, 2025)

Facile fabrication of MnCO3 and covalent organic framework on the surface of MXene with sodium alginate hydrogel for effective photocatalytic eradication of disinfected byproducts - Saleem Raza; Cheng Chen; Wei Yu; Muslim Raza; Malik Taj Ahmad; Nisha Singh; Liguo Shen; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Refinement of vehicle emission factor estimation in tunnel experiments using CFD and field measurement - Xiaoyu Liang; Jianfei Peng; Yan Liu; Jinsheng Zhang; Lin Wu; Hongjun Mao (Environmental Pollution, 2025)

Novel CoMo-LDH integration enhanced permeability and self-cleaning of MXene-based membrane for efficient water treatment - Qianqian Zeng; Zhiyu Zhao; Yue Wang; Siyuan Chen; Hua Li; Cheng Chen; Wei Yu; Jiaheng Teng; Hongjun Lin; Yu Yang; Liguo Shen (Chemical Engineering Journal, 2025)

Stable molecular-bridged graphene oxide membrane with bioinspired hydrophilic water inlets for ultrafast molecular separation - Boya Wang; Cheng Chen; Wei Yu; Jiujing Xu; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Membrane technology for microplastic removal: Microplastic occurrence, challenges, and innovations of process and materials - Zhuoran Lin; Xingyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Wei Yu; Bisheng Li; Leihong Zhao; Mingyi Ying (Chemical Engineering Journal, 2025)

Deciphering the nexus of soluble microbial products (SMPs) and membrane fouling: Roles, mechanisms, and control strategies - Xinyu Hu; Hongjun Lin; Genying Yu; Liguo Shen; Jiaheng Teng; Meijia Zhang; Bisheng Li; Leihong Zhao; Die ling Zhao; Cheng Chen (Chemical Engineering Journal, 2025)

Bio-derived carboxymethyl cellulose-graft-gallic acid antiscalant with remarkable antibacterial activity for reverse osmosis scaling and biofouling control - Liping Xiong; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Liguo Shen (Water Research, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Pioneering integration of bimetallic Fe2O3-Mn2O3 nanoparticles into polyamide nanofiltration membranes for enhanced antibiotic wastewater treatment - Yidan Ding; Hanchen Zhang; Liguo Shen; Yang Jiao; Yanchao Xu; Hongjun Lin (Journal of Cleaner Production, 2025)

Alternating current electrochemistry for energy-efficient contaminant removal and resource recovery in water treatment: A critical review - Chengyue Yu; Cheng Chen; Mingzhu Zhou; Bisheng Li; Leihong Zhao; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2025)

Enhancing oil/water emulsion separation with inkjet printed beetle-inspired zeolitic imidazolate framework-67 modified membranes - Xinyu Hu; Hongli Xie; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin; Leihong Zhao; Genying Yu (Desalination, 2025)

Tea tree oil Pickering emulsions stabilized by sodium lignosulfonate-zein covalent conjugate for fungicide delivery and enhanced control efficacy against peanut sclerotium blight - Jihao Zuo; Yitong Lin; Jiayuan Tian; Jinting Cai; Li Hao; Dongjie Liu; Qin Wang; Gengsheng Xiao; Xinhua Zhou; Hongjun Zhou (Chemical Engineering Journal, 2025)

Laboratory measurement and machine learning-based analysis of driving factors for brake wear particle emissions from light-duty electric vehicles and heavy-duty vehicles - Jiawei Yin; Zhou Xu; Wendi Wei; Zhenyu Jia; Tiange Fang; Zhiwen Jiang; Zeping Cao; Lin Wu; Ning Wei; Zhengyu Men; Quanyou Guo; Qijun Zhang; et al. (Journal of Hazardous Materials, 2025)

A synergistic approach integrating potassium ferrate oxidation with polyacrylamide flocculation to enhance sludge dewatering and its mechanisms - Yansha Zeng; Yue Shen; Hongjun Lin; Qiyin Tan; Jiahao Sun; Liguo Shen; Renjie Li; Yanchao Xu; Jiaheng Teng (Journal of Environmental Management, 2025)

Membrane fouling behaviors of microplastic in coagulation-ultrafiltration process: Role of surface functional groups - Yue Shen; Tao Jian; Genying Yu; Hongjun Lin; Xiang Cai; Liguo Shen; Zengjian Zhao; Leihong Zhao; Meijia Zhang; Die Ling Zhao; Bisheng Li (Chemical Engineering Journal, 2025)

Glycerol-driven optimization of algae-bacteria symbiosis systems for enhanced lipid production and self-flocculation - Yuwei Zhang; Jiaheng Teng; Jiahui Huang; Liguo Shen; Hongjun Lin; Renjie Li; Xiang Cai; Zeqiong Xu; Meijia Zhang (Journal of Environmental Chemical Engineering, 2025)

Green β-cyclodextrin interlayered crumpled polyamide membranes for effective desalination - Jian Yu; Ling Zhang; Hongguang Sun; Renjie Li; Die Ling Zhao; Liguo Shen; Hongjun Lin; Yang Jiao; Yanchao Xu (Desalination, 2025)

Illuminating for purity: Photocatalytic and photothermal membranes for sustainable oil-water separation - Hongyuan Zhu; Zhenyu Guo; Wei Yu; Shasha Yuan; Liguo Shen; Die Ling Zhao; Hongjun Lin (Water Research, 2025)

Size distribution, chemical composition and influencing factors of vehicle tire wear particles based on a novel test cycle - Qijun Zhang; Jiawei Yin; Zeping Cao; Tiange Fang; Jianfei Peng; Lin Wu; Hongjun Mao (Environmental Research, 2025)

Sustainable transportation emission reduction through intelligent transportation systems: Mitigation drivers, and temporal trends - Zhenyu Jia; Jiawei Yin; Zeping Cao; Ning Wei; Zhiwen Jiang; Yanjie Zhang; Lin Wu; Qijun Zhang; Hongjun Mao (Environmental Impact Assessment Review, 2025)

Comparison of vehicular emissions at different altitudes: Characteristics and policy implications - Zhiwen Jiang; Haomiao Niu; Zhenyu Jia; Lin Wu; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Environmental Pollution, 2025)

In-situ micelle-guided fabrication of porous iron oxide membranes for superior dye separation - Sijin Wu; Zhe Wang; Zhenxiang Pan; Qian Lei; Tao Jian; Wen Lu; Zengjian Zhao; Hongjun Lin (Chemical Engineering Journal, 2025)

A single-atom manganese nanozyme mediated membrane reactor for water decontamination - Jiahao Sun; Minjia Yan; Guangdong Tao; Runbin Su; Xuanming Xiao; Qiangshun Wu; Feng Chen; Xi-Lin Wu; Hongjun Lin (Water Research, 2025)

Photothermal nano-confinement reactor with bimetallic sites for enhanced peroxymonosulfate activation in antibiotic degradation - Hao Wang; Yuzhen Cao; Bisheng Li; Liguo Shen; Xi-Lin Wu; Renjie Li; Hongjun Lin (Water Research, 2025)

Strengthening peroxymonosulfate activation via cotton-derived carbon: Pathway transformation from radical to non-radical - Runbin Su; Yonglin Ma; Lei Liu; Qiangshun Wu; Du Fu; Yu Li; Hongjun Lin; Xiaoxuan Wei; Muhammad Saboor Siddique; Jianrong Chen; Xi-Lin Wu (Journal of Cleaner Production, 2025)

Novel insights into halogenated carbazoles (HCZs) prediction in tap water: A comparative study of grey relational analysis-based neural networks - Qianfeng He; Wanting Xu; Guolong Chen; Zhen Wang; Yan Liang; Hongjie Sun; Huachang Hong; Hongjun Lin; Zeqiong Xu (Journal of Cleaner Production, 2025)

Versatile electrospun cobalt-doped carbon films for rapid antibiotic degradation - Hao Wang; Yuzhen Cao; Liguo Shen; Xi-Lin Wu; Die ling Zhao; Renjie Li; Hongjun Lin (Journal of Environmental Management, 2025)

Spatiotemporal distribution prediction for PM2.5 based on STXGBoost model and high-density monitoring sensors in Zhengzhou High Tech Zone, China - Shiqi Zhao; Hong Lin; Hongjun Wang; Gege Liu; Xiaoning Wang; Kailun Du; Ge Ren (Journal of Environmental Management, 2025)

The heterointerface engineering triggers hydrogen spillover through synergistic effect in alkaline media - Qiang Zhang; Yuhong Bian; Sunpeng Shan; Zhiwei Shu; Nana Wang; Xiao Zhang; Yanchao Xu; Hongjun Lin; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2025)

Membrane fouling characteristics and mechanisms in coagulation-ultrafiltration process for treating microplastic-containing water - Yue Shen; Qiyin Tan; Jiahao Sun; Xiang Cai; Liguo Shen; Hongjun Lin; Xiaoxuan Wei (Science of The Total Environment, 2024)

Membrane fouling mechanisms in the presence of microplastics and organic matter: The unexpected mitigating role of Ca2+ - Xiaoni Zhou; Wenfa Yang; Hongjun Lin; Biyan Wang; Mingjing Xie; Hao Fang; Hanmin Zhang; Meijia Zhang; Jiaheng Teng (Science of The Total Environment, 2024)

Super-hydrophilic membranes fabricated by synergistic integration of covalent organic framework nanoflowers and hydrophilic layers for efficient oil-water separation - Baoliang Dai; Yidan Ding; Cheng Chen; Liguo Shen; Die Ling Zhao; Yang Jiao; Hongjun Lin; Yanchao Xu (Desalination, 2024)

Recent progress in green thin film membrane based materials for desalination: Design, properties and applications - Saleem Raza; Asif Hayat; Tariq Bashir; Ehsan Ghasali; Amal A. Abdel Hafez; Cheng Chen; Liguo Shen; Yasin Orooji; Hongjun Lin (Desalination, 2024)

Effects of calcium ions and polysaccharides type on transparent exopolymer particle formation and the related fouling mechanisms - Qiyin Tan; Yue Shen; Jiahao Sun; Tao Jian; Wen Lu; Sijin Wu; Zengjian Zhao; Qian Lei; Hongjun Lin (Science of The Total Environment, 2024)

Large-scale deployment of intelligent transportation to help achieve low-carbon and clean sustainable transportation - Zhenyu Jia; Jiawei Yin; Zeping Cao; Ning Wei; Zhiwen Jiang; Yanjie Zhang; Lin Wu; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Activation of peroxymonosulfate by novel magnetically recyclable CoFe2O4/MXene quantum dots composites for rapid degradation of tetracycline: Synergistic performance and mechanisms - Zhenyu Guo; Haiyi Jin; Hongyu Sun; Bisheng Li; Huadong Yu; Die Ling Zhao; Hongjun Lin (Journal of Environmental Management, 2024)

Efficient nitrogen removal and stable operation of a dynamic membrane bioreactor (DMBR) for landfill leachate treatment - Jie Han; Wei Xu; Junjie Zhu; Xiaomei Su; Hailu Fu; Xiao Xiao; Feng Dong; Chongjun Chen; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2024)

Optimization of microalgal-bacterial consortium flocculation through chitosan-diatomite composite materials: A sustainable approach to biomass harvesting - Yu Zhao; Qian Lei; Jiaheng Teng; Xiu Zhang; Hongjun Lin; Meijia Zhang (Chemical Engineering Journal, 2024)

Consolidating CQDs with NiFe-MOF photo-Fenton membranes to effectively treat wastewater containing antibiotics and antibiotic-resistant bacteria - Haiyi Jin; Wangyi Zhou; Zhenyu Guo; Hailiang Xu; Xiaoli Zhong; Tai-Shung Chung; Die Ling Zhao; Hongjun Lin (Chemical Engineering Journal, 2024)

Quasi-FeCo-MOF/CoS amorphous Nanosheets: A stable and highly active catalyst for electrocatalytic water splitting and monosaccharide oxidation - Yanqiu Xu; Qiang Zhang; Nana Wang; Lijun Huang; Xiao Zhang; Hongjun Lin; Yanchao Xu; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2024)

Amentoflavone Induces Ferroptosis to Alleviate Proliferation, Migration, Invasion and Inflammation in Rheumatoid Arthritis Fibroblast-like Synoviocytes by Inhibiting PIN1 - Yan Ma; Hongjun Lin; Yunman Li; Zhuoling An (Cell Biochemistry and Biophysics, 2024)

A synergistic approach combining computational fluid dynamics simulation with hydrolysis-acidification for dye wastewater treatment - Zhe Wang; Yansha Zeng; Zhenxiang Pan; Liguo Shen; Bizhen Zeng; Jiaheng Teng; Hongjun Lin (Journal of Environmental Management, 2024)

Enhanced sludge dewatering using a novel synergistic iron/peroxymonosulfate-polyacrylamide method - Yansha Zeng; Zhe Wang; Qiyin Tan; Yue Shen; Jiahao Sun; Liguo Shen; Jiaheng Teng; Hongjun Lin (Journal of Environmental Management, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

Predicting thermodynamic adhesion energies of membrane fouling in planktonic anammox MBR via backpropagation neural network model - Xiang Cai; Si Pang; Meijia Zhang; Jiaheng Teng; Hongjun Lin; Siqing Xia (Bioresource Technology, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

How temporary disruption of metro service influence metro commuters’ mode shifts during the COVID-19 pandemic? Evidence from Tianjin, China - Xinwei Ma; Shaofan Sun; Lin Li; Mingjia He; Hongjun Cui (Travel Behaviour and Society, 2024)

Innovative treatment of industrial effluents through combining ferric iron and attapulgite application - Zhenxiang Pan; Bizhen Zeng; Liguo Shen; Jiaheng Teng; Tongli Lai; Leihong Zhao; Genying Yu; Hongjun Lin (Chemosphere, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Selenium in plants: A nexus of growth, antioxidants, and phytohormones - Sufian Ikram; Yang Li; Chai Lin; Debao Yi; Wang Heng; Qiang Li; Lu Tao; Yu Hongjun; Jiang Weijie (Journal of Plant Physiology, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Atmospheric environment characteristic of severe dust storms and its impact on sulfate formation in downstream city - Naixiu Sun; Lin Wu; Fangyuan Zheng; Danni Liang; FuYuan Qi; Shaojie Song; Jianfei Peng; Yufen Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Mg2+ addition: Unlocking optimized treatment performance and anti-fouling property in microalgal-bacterial membrane bioreactors - Fei Huang; Yu Zhao; Shilei Chen; Hongjun Lin; Jiaheng Teng; Xiang Cai; Meijia Zhang (Science of The Total Environment, 2024)

Emerging disinfection byproducts 3-bromine carbazole induces cardiac developmental toxicity via aryl hydrocarbon receptor activation in zebrafish larvae - Yingying Liu; Xudong Jin; Yanan Ye; Zeqiong Xu; Zhongkun Du; Huachang Hong; Haiying Yu; Hongjun Lin; Xianfeng Huang; Hongjie Sun (Environmental Pollution, 2024)

Advances in synthesis and application of amphoteric polymer-based water treatment agents - Wei Yu; Liping Xiong; Jiaheng Teng; Cheng Chen; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Desalination, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Residues of Polycyclic Aromatic Hydrocarbons in Breast Milk Collected from Jinhua (China) and the Influence of Exercise Habit: Levels and the Potential Health Effects - Qianfeng He; Xiaoge Zhang; Lihong Kuang; Haotian Xu; Yizhong Hou; Fangqu Huang; Zeqiong Xu; Hongjie Sun; Wenjing Deng; Hongjun Lin; Huachang Hong (Exposure and Health, 2024)

New directions on membranes for removal and degradation of emerging pollutants in aqueous systems - Die Ling Zhao; Wangyi Zhou; Liguo Shen; Bowen Li; Hongyu Sun; Qianqian Zeng; Chuyang Y. Tang; Hongjun Lin; Tai-Shung Chung (Water Research, 2024)

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Investigating the impact of high-altitude on vehicle carbon emissions: A comprehensive on-road driving study - Zhiwen Jiang; Lin Wu; Haomiao Niu; Zhenyu Jia; Zhaoyu Qi; Yan Liu; Qijun Zhang; Ting Wang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2024)

Regenerative braking system effectively reduces the formation of brake wear particles - Qijun Zhang; Jiawei Yin; Tiange Fang; Quanyou Guo; Jiaxing Sun; Jianfei Peng; Chongzhi Zhong; Lin Wu; Hongjun Mao (Journal of Hazardous Materials, 2024)

New insights into survival strategies and PCB bioremediation potential of resuscitated strain Achromobacter sp. HR2 under combined stress conditions - Jie Shi; Yingying Yang; Shusheng Zhang; Qihua Lin; Faqian Sun; Hongjun Lin; Chaofeng Shen; Xiaomei Su (Journal of Hazardous Materials, 2024)

Novel combination of iron-carbon composite and Fenton oxidation processes for high-concentration antibiotic wastewater treatment - Zhe Wang; Yansha Zeng; Qiyin Tan; Yue Shen; Liguo Shen; Jiahao Sun; Leihong Zhao; Hongjun Lin (Journal of Environmental Management, 2024)

Unveiling the PCB biodegradation potential and stress survival strategies of resuscitated strain Pseudomonas sp. HR1 - Yingying Yang; Qian Zhang; Qihua Lin; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Environmental Pollution, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Harnessing diurnal dynamics: Deciphering the interplay of light cycles on algal-bacterial membrane bioreactors - Sihan Cheng; Yuwei Zhang; Yu Zhao; Xin Hu; Hongjun Lin; Jiaheng Teng; Meijia Zhang (Science of The Total Environment, 2024)

Atomically dispersed dual-atom catalysts: A new rising star in environmental remediation - Xialiang Jiang; Cheng Chen; Junjie Chen; Shuning Yu; Wei Yu; Liguo Shen; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Science of The Total Environment, 2024)

Enhanced management and antifouling performance of a novel NiFe-LDH@MnO2/PVDF hybrid membrane for efficient oily wastewater treatment - Kai Fan; Ning Kong; Jing Ma; Hongjun Lin; Chuanyang Gao; Jinshen Lei; Zihang Zeng; Jun Hu; Juncheng Qi; Liguo Shen (Journal of Environmental Management, 2024)

Direct measurement of brake and tire wear particles based on real-world driving conditions - Qijun Zhang; Tiange Fang; Zhengyu Men; Ning Wei; Jianfei Peng; Tianqiang Du; Xinfeng Zhang; Yao Ma; Lin Wu; Hongjun Mao (Science of The Total Environment, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

Innovative construction of nano-wrinkled polyamide membranes using covalent organic framework nanoflowers for efficient desalination and antibiotic removal - Baoliang Dai; Yijing Hu; Yidan Ding; Liguo Shen; Renjie Li; Dieling Zhao; Yang Jiao; Yanchao Xu; Hongjun Lin (Desalination, 2024)

Flexible metal membrane integrated electrified and catalytic attributes for multifunctional water purification with enhanced scaling resistance - Ning Kong; Liguo Shen; Qianqian Zeng; Cheng Chen; Jiaheng Teng; Feng Chen; Hongjun Lin (Chemical Engineering Journal, 2024)

Effective strategies for reclamation of saline-alkali soil and response mechanisms of the soil-plant system - Xin Xu; Lin Guo; Shaobo Wang; Xuanyi Wang; Meng Ren; Pengjie Zhao; Ziyi Huang; Hongjun Jia; Jinhang Wang; Aijun Lin (Science of The Total Environment, 2023)

Membrane-catalysis integrated system for contaminants degradation and membrane fouling mitigation: A review - Cheng Chen; Lun Lu; Lingya Fei; Jiujing Xu; Boya Wang; Bisheng Li; Liguo Shen; Hongjun Lin (Science of The Total Environment, 2023)

Comprehensive evaluation of the risk system for heavy metals in the rehabilitated saline-alkali land - Xin Xu; Lin Guo; Shaobo Wang; Meng Ren; Pengjie Zhao; Ziyi Huang; Hongjun Jia; Jinhang Wang; Aijun Lin (Journal of Environmental Management, 2023)

A low-cost and sustainable solution for nitrate removal from secondary effluent: Macroporous ion exchange resin treatment - Bizhen Zeng; Bingchi Tao; Zhenxiang Pan; Liguo Shen; Jianzhen Zhang; Hongjun Lin (Journal of Environmental Management, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Optimizing aeration intensity to enhance self-flocculation in algal-bacterial symbiosis systems - Jiahui Huang; Sihan Cheng; Yuwei Zhang; Jiaheng Teng; Meijia Zhang; Hongjun Lin (Chemosphere, 2023)

Unlocking the potential of resuscitation-promoting factor for enhancing anaerobic microbial dechlorination of polychlorinated biphenyls - Zhen Han; Aiqin Hou; Xiaolin Cai; Mengqi Xie; Faqian Sun; Chaofeng Shen; Hongjun Lin; Haiying Yu; Xiaomei Su (Science of The Total Environment, 2023)

Chemical characteristics of fine tire wear particles generated on a tire simulator - Quanyou Guo; Zhengyu Men; Zhenguo Liu; Zhihui Niu; Tiange Fang; Fengyang Liu; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

A sustainable solution for organic pollutant degradation: Novel polyethersulfone/carbon cloth/FeOCl composite membranes with electric field-assisted persulfate activation - Jing Wang; Hao Wang; Liguo Shen; Renjie Li; Hongjun Lin (Water Research, 2023)

The combination of multiple linear regression and adaptive neuro-fuzzy inference system can accurately predict trihalomethane levels in tap water with fewer water quality parameters - Jianzhen Zhang; Duo Ye; Quanyou Fu; Minjie Chen; Hongjun Lin; Xiaoling Zhou; Wenjing Deng; Zeqiong Xu; Hongjie Sun; Huachang Hong (Science of The Total Environment, 2023)

Green light optimized speed advisory achieves fuel savings and CO2 emission reduction by profoundly impacting driving behavior - Xiaoyang Zhao; Zhenyu Jia; Ning Wei; Dongping Guo; Lu Yao; Jiawei Yin; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Anaerobic biodegradation of anthraquinone dye reactive black 19 by a resuscitated strain Bacillus sp. JF4: Performance and pathway - Qian Zhang; Yuyang Wang; Mayada Jamal; Rui Wang; Qiuyang He; Faqian Sun; Hongjun Lin; Xiaomei Su (Journal of Environmental Chemical Engineering, 2023)

Enhanced denitrification performance of granular sludge for the treatment of waste brine from ion exchange resin process - Zhenxiang Pan; Zhongqiang Li; Bizhen Zeng; Liguo Shen; Hongjun Lin (Journal of Environmental Management, 2023)

Novel thermodynamic mechanisms of co-conditioning with polymeric aluminum chloride and polyacrylamide for improved sludge dewatering: A paradigm shift in the field - Yansha Zeng; Zhe Wang; Zhenxiang Pan; Liguo Shen; Jiaheng Teng; Hongjun Lin; Jianzhen Zhang (Environmental Research, 2023)

Nano-wrinkled polyamide membrane preparation via heterogeneous surface-regulated interfacial polymerization for enhanced desalination performance - Zhiwen Li; Yanchao Xu; Liguo Shen; Renjie Li; Yang Jiao; Hongjun Lin; Chuyang Y. Tang (Desalination, 2023)

Innovative role of polyvinylpyrrolidone in tailoring polyamide layer for high-performance nanofiltration membranes - Zhiwen Li; Shuilian Peng; Wentian Zhang; Jianzhen Zhang; Yang Jiao; Renjie Li; Liguo Shen; Hongjun Lin; Yanchao Xu (Desalination, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Enhanced methane yield in anaerobic digestion of waste activated sludge by combined pretreatment with fungal mash and free nitrous acid - Min Zhang; Yuwei Yang; Huaqian Mou; Aodong Pan; Xiaomei Su; Jianrong Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2023)

Superior performance of a membrane bioreactor through innovative in-situ aeration and structural optimization using computational fluid dynamics - Liguo Shen; Qihang Wu; Qunfeng Ye; Hongjun Lin; Jianzhen Zhang; Cheng Chen; Rong Yue; Jiaheng Teng; Huachang Hong; Bao-Qiang Liao (Water Research, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Heavy vehicles’ non-exhaust exhibits competitive contribution to PM2.5 compared with exhaust in port and nearby areas - Tiange Fang; Ting Wang; Chao Zou; Quanyou Guo; Jianhua Lv; Yanjie Zhang; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Characteristics, sources, and health risks of inorganic elements in PM2.5 and PM10 at Tianjin Binhai international airport - Qijun Zhang; Lei Yang; Jianfei Peng; Lin Wu; Hongjun Mao (Environmental Pollution, 2023)

Feasibility and optimization of a novel upflow denitrification reactor using denitrifying granular sludge for nitric acid pickling wastewater treatment - Bizhen Zeng; Yanhong Jiang; Zhenxiang Pan; Liguo Shen; Hongjun Lin (Bioresource Technology, 2023)

Novel cetyltrimethylammonium bromide modified mixed adsorbent for efficient treatment of dyeing and printing wastewater - Zhenxiang Pan; Mohan Song; Bizhen Zeng; Liguo Shen; Leihong Zhao; Hongjun Lin (Process Safety and Environmental Protection, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Energy saving and emission reduction effects from the application of green light optimized speed advisory on plug-in hybrid vehicle - Zhenyu Jia; Ning Wei; Jiawei Yin; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Phenol degradation at high salinity by a resuscitated strain Pseudomonas sp. SAS26: kinetics and pathway - Shusheng Zhang; Zijing An; Xiaomei Su; Aiqin Hou; Leilei Liu; Lihua Zhang; Qiuyang He; Faqian Sun; Zupei Lei; Hongjun Lin; Jiahou Lai (Journal of Environmental Chemical Engineering, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Anaerobic membrane bioreactor for the treatment of high-strength waste/wastewater: A critical review and update - Zijing An; Junjie Zhu; Min Zhang; Yan Zhou; Xiaomei Su; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2023)

Brevicalamide, a new anthranilamide from Aconitum brevicalcaratum, suggests a new type of chemotaxonomic marker for tribe Delphineae - Mao Lin; Zhainan Zhang; Shining Cai; Hongjun Jiang; Tianpeng Yin (Biochemical Systematics and Ecology, 2023)

Softening/Hardening Damage Model and Numerical Implementation of Seabed Silt-Steel Interface in Yellow River Underwater Delta - Peng Yu; Honghua Liu; Lin Geng; Shuai Wang; Yang Yu; Chenghao Zhu; Qi Yang; Hongjun Liu; Yong Guan (Journal of Marine Science and Engineering, 2023)
The interaction between soil and structure is a research hotspot in ocean engineering, and the shear performance of interfaces is an essential factor affecting the bearing capacity of offshore structures. Taking the Yellow River Underwater Delta as the research area, the Softening/Hardening damage model of the silt–steel interface and the determination method of model parameters are proposed based on the statistical damage theory. Through the interface monotonic shear test under the conditions of different normal stress, roughness and water content, the shear mechanical properties and volumetric deformation laws on the silt–steel interface are analyzed, and the damage model parameters are obtained. Finally, a FRIC subroutine for the damage model was developed based on ABAQUS. The research results indicate the following: (1) The interface between silt and steel exhibits two characteristics, softening/hardening and shear shrinkage/expansion, under different conditions. Roughness significantly impacts interfacial cohesion, while water content mainly affects the internal friction angle. (2) The softening model based on the classic rock damage model can better simulate the stress–strain relationship of the silt–steel interface under high normal stress and low water content. In contrast, the hardening model based on the classic hyperbola model can better simulate the stress–strain relationship under low normal stress and high water content. The calculated results of the softening/hardening model agree with the experimental results, and the model has 7 parameters. (3) The developed FRIC subroutine can effectively simulate the nonlinear mechanical behavior of the interface between silt and steel. The research results provide a reference for exploring the stability analysis of offshore structures considering interface weakening effects.

Efficient oily wastewater treatment by a novel electroflotation-membrane separation system consisting a Ni-Cu-P membrane prepared by electroless nickel plating - Jing Wang; Binghong Chen; Hongjun Lin; Renjie Li (Science of The Total Environment, 2023)

Comparation of mesophilic and thermophilic anaerobic co-digestion of food waste and waste activated sludge driven by biochar derived from kitchen waste - Rong Zhang; Min Zhang; Huaqian Mou; Zijing An; Hailu Fu; Xiaomei Su; Chongjun Chen; Jianrong Chen; Hongjun Lin; Faqian Sun (Journal of Cleaner Production, 2023)

Standard environmental evaluation framework reveals environmental benefits of green light optimized speed advisory: A case study on plug-in hybrid electric vehicles - Ning Wei; Zhenyu Jia; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Investigation on dynamic performance of wind turbines using different scaling methods in wind tunnel tests - Kun Lin; Shaohui Xiao; Hongjun Liu; Annan Zhou (Engineering Structures, 2023)

Surface selenation engineering on metal cocatalysts for highly efficient photoreduction of carbon dioxide to methanol - Wenbin Chen; Shijie Wu; Liyan Xie; Yujie Wu; Yanwen Ye; Huigang Wang; Zhulei Chen; Hongjun Lin; Leihong Zhao; Song Bai (Chemical Engineering Journal, 2023)

Mitigating soil salinity stress with titanium gypsum and biochar composite materials: Improvement effects and mechanism - Xin Xu; Jiahui Wang; Yiming Tang; Xuedan Cui; Daibing Hou; Hongjun Jia; Shaobo Wang; Lin Guo; Jinhang Wang; Aijun Lin (Chemosphere, 2023)

Simultaneous adsorption and biodegradation of polychlorinated biphenyls using resuscitated strain Streptococcus sp. SPC0 immobilized in polyvinyl alcohol‑sodium alginate - Qihua Lin; Jiayan Ding; Yingying Yang; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Science of The Total Environment, 2023)

A novel strategy for enhancing bioremediation of polychlorinated biphenyl-contaminated soil with resuscitation promoting factor and resuscitated strain - Xinru Zhou; Shusheng Zhang; Rui Wang; Zijing An; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Journal of Hazardous Materials, 2023)

Algae extract delamination of molybdenum disulfide and surface modification with glycidyl methacrylate and polyaniline for the elimination of metal ions from wastewater - Saleem Raza; Muhammad Usman Hameed; Ehsan Ghasali; Asif Hayat; Yasin Orooji; Hongjun Lin; Ceren Karaman; Fatemeh Karimi; Nevin Erk (Environmental Research, 2023)

Advances in technology and utilization of natural resources for achieving carbon neutrality and a sustainable solution to neutral environment - Saleem Raza; Ehsan Ghasali; Muslim Raza; Cheng Chen; Bisheng Li; Yasin Orooji; Hongjun Lin; Ceren Karaman; Hassan Karimi Maleh; Nevin Erk (Environmental Research, 2023)

Graphene oxide assisted assembly of superhydrophilic MOF-based membrane with 2D/3D hybrid nanochannels for enhanced water purification - Lingya Fei; Cheng Chen; Liguo Shen; Yuyao Zhang; Boya Wang; Jiujing Xu; Bisheng Li; Saleem Raza; Hongjun Lin (Chemical Engineering Journal, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

High propensity of membrane fouling and the underlying mechanisms in a membrane bioreactor during occurrence of sludge bulking - Mengfei Wu; Meijia Zhang; Liguo Shen; Xinhua Wang; Deng Ying; Hongjun Lin; Renjie Li; Yanchao Xu; Huachang Hong (Water Research, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Comparison of CO2, NOx, and VOCs emissions between CNG and E10 fueled light-duty vehicles - Zongyan Lv; Lin Wu; Chao Ma; Luna Sun; Jianfei Peng; Lei Yang; Ning Wei; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2023)

Two dimensional (2D) materials and biomaterials for water desalination; structure, properties, and recent advances - Saleem Raza; Ehsan Ghasali; Yasin Orooji; Hongjun Lin; Ceren Karaman; Elena Niculina Dragoi; Nevin Erk (Environmental Research, 2023)

Engineering metal–organic frameworks (MOFs) based thin-film nanocomposite (TFN) membranes for molecular separation - Die Ling Zhao; Fan Feng; Liguo Shen; Zhengyi Huang; Qipeng Zhao; Hongjun Lin; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Mitigation of protein fouling by magnesium ions and the related mechanisms in ultrafiltration process - Hui Zou; Jiahui Huang; Meijia Zhang; Hongjun Lin; Jiaheng Teng; Zhengyi Huang (Chemosphere, 2023)

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

The coupling of persulfate activation and membrane separation for the effective pollutant degradation and membrane fouling alleviation - Mingzhu Zhou; Junjie Chen; Shuning Yu; Binghong Chen; Cheng Chen; Liguo Shen; Bisheng Li; Hongjun Lin (Chemical Engineering Journal, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

Study on Particle Size Distribution Characteristics in Urban Roadside Microenvironment Using an ELPI+ - Xiaozhen Fang; Lin Wu; Qijun Zhang; Jing Zhang; Zhiwen Yang; Chao Zou; Chao Ma; Yanjie Zhang; Hongjun Mao (Water, Air, & Soil Pollution, 2022)

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

The influence of socioeconomic and environmental determinants on acute myocardial infarction (AMI) mortality from the spatial epidemiological perspective - Yan Wang; Bin Guo; Lin Pei; Hongjun Guo; Dingming Zhang; Xuying Ma; Yan Yu; Haojie Wu (Environmental Science and Pollution Research, 2022)

PM2.5-PAHs and PM10-PAHs at roadside environment: levels, meteorological impact, source apportionment, and health risks - Qijun Zhang; Lei Yang; Yanjie Zhang; Xiaozhen Fang; Lin Wu; Hongjun Mao (Air Quality, Atmosphere & Health, 2022)

Emission inventory and control policy for non-road construction machinery in Tianjin - Qijun Zhang; Ning Wei; Lei Yang; Xi Feng; Yanjie Zhang; Lin Wu; Hongjun Mao (Environmental Science and Pollution Research, 2022)

Productivity calculating method in tight gas reservoirs considering the stress sensitivity - Jie He; Xiangdong Guo; Hongjun Cui; Kaiyu Lei; Yanyun Lei; Lin Zhou; Qinghai Liu; Yushuang Zhu; Linyu Liu (Arabian Journal of Geosciences, 2022)

Do air pollutants as well as meteorological factors impact Corona Virus Disease 2019 (COVID-19)? Evidence from China based on the geographical perspective - Lin Pei; Xiaoxia Wang; Bin Guo; Hongjun Guo; Yan Yu (Environmental Science and Pollution Research, 2021)

Patients with first-episode untreated schizophrenia who experience concomitant visual disturbances and auditory hallucinations exhibit co-impairment of the brain and retinas—a pilot study - Chuanjun Zhuo; Bo Xiao; Feng Ji; Xiaodong Lin; Deguo Jiang; Hongjun Tian; Yong Xu; Wenqiang Wang; Ce Chen (Brain Imaging and Behavior, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Strategies to solve the reverse inference fallacy in future MRI studies of schizophrenia: a review - Chuanjun Zhuo; Gongying Li; Xiaodong Lin; Deguo Jiang; Yong Xu; Hongjun Tian; Wenqiang Wang; Xueqin Song (Brain Imaging and Behavior, 2021)
Few advances in schizophrenia research have been translated into clinical practice, despite 60 years of serum biomarkers studies and 50 years of genetic studies. During the last 30 years, neuroimaging studies on schizophrenia have gradually increased, partly due to the beautiful prospect that the pathophysiology of schizophrenia could be explained entirely by the Human Connectome Project (HCP). However, the fallacy of reverse inference has been a critical problem of the HCP. For this reason, there is a dire need for new strategies or research “bridges” to further schizophrenia at the biological level. To understand the importance of research “bridges,” it is vital to examine the strengths and weaknesses of the recent literature. Hence, in this review, our team has summarized the recent literature (1995–2018) about magnetic resonance imaging (MRI) of schizophrenia in terms of regional and global structural and functional alterations. We have also provided a new proposal that may supplement the HCP for studying schizophrenia. As postulated, despite the vast number of MRI studies in schizophrenia, the lack of homogeneity between the studies, along with the relatedness of schizophrenia with other neurological disorders, has hindered the study of schizophrenia. In addition, the reverse inference cannot be used to diagnose schizophrenia, further limiting the clinical impact of findings from medical imaging studies. We believe that multidisciplinary technologies may be used to develop research “bridges” to further investigate schizophrenia at the single neuron or neuron cluster levels. We have postulated about future strategies for overcoming the current limitations and establishing the research “bridges,” with an emphasis on multimodality imaging, molecular imaging, neuron cluster signals, single transmitter biomarkers, and nanotechnology. These research “bridges” may help solve the reverse inference fallacy and improve our understanding of schizophrenia for future studies.

Differences in functional connectivity density among subtypes of schizophrenic auditory hallucination - Chuanjun Zhuo; Gongying Li; Feng Ji; Ce Chen; Deguo Jiang; Xiaodong Lin; Yong Xu; Hongjun Tian; Lina Wang; Chunhua Zhou; Xiao Lin (Brain Imaging and Behavior, 2020)

Without insight accompanied with deteriorated brain functional alterations in healthy individuals with auditory verbal hallucinations: a pilot study - Chuanjun Zhuo; Feng Ji; Xiaodong Lin; Hongjun Tian; Lina Wang; Sha Liu; Hong Sang; Wenqiang Wang; Chunmian Chen (Brain Imaging and Behavior, 2020)
Few studies have reported on brain functional differences between healthy individuals with auditory verbal hallucinations (Hi-AVH) with and without insight, so we designed a study to address this knowledge gap. We enrolled 12 Hi-AVH with insight, 15 Hi-AVH without insight, and 15 AVH-free controls (Healthy controls). Global functional connectivity density (gFCD) mapping was used to estimate brain networks. We found that the most common alterations in both Hi-AVH groups were increased gFCD in superior parietal lobule and superior temporal gyrus. We also found that distinct brain functional patterns of Hi-AVH without insight comprised lower gFCD in the frontal lobe oculomotor area, dorsolateral prefrontal cortex, supramarginal gyrus, primary auditory cortex, sensorimotor cortex, ventral anterior, and posterior cingulate Our pilot findings support the hypothesis that abnormal reciprocal action in the circuits for processing perception, memory, language, and attentional control may be pathological features of auditory verbal hallucinations.

Comprehensive Investigation and Assessment of Nutrient and Heavy Metal Contamination in the Surface Water of Coastal Bohai Sea in China - Heshan Lin; Hongjun Li; Xiaolong Yang; Zizhou Xu; Yindong Tong; Xingguang Yu (Journal of Ocean University of China, 2020)

Magnetic properties indicate the sources of hadal sediments in the Yap Trench, northwest Pacific Ocean - Yu Chen; Jichao Yang; Olusegun A. Dada; Yaomin Yang; Zhen Lin; Zhen Cui; Yue Xu; Hongjun Yu; Baohua Liu (Journal of Oceanology and Limnology, 2020)

Enzyme and pH dual-responsive avermectin nano-microcapsules for improving its efficacy - Guanghua Liu; Guanquan Lin; Xida Lin; Hongjun Zhou; Huayao Chen; Li Hao; Xinhua Zhou (Environmental Science and Pollution Research, 2019)

Control of NOx emissions by air staging in small- and medium-scale biomass pellet boilers - Yuening Li; Yingchao Lin; Jingbo Zhao; Boyang Liu; Ting Wang; Peng Wang; Hongjun Mao (Environmental Science and Pollution Research, 2019)

Population genetic patterns of the solitary tunicate, Molgula manhattensis, in invaded Chinese coasts: large-scale homogeneity but fine-scale heterogeneity - Yiyong Chen; Shiguo Li; Yaping Lin; Hongjun Li; Aibin Zhan (Marine Biodiversity, 2018)

Phytoplankton pigment pattern in the subsurface chlorophyll maximum in the South Java coastal upwelling system, Indonesia - Chunlei Gao; Mingzhu Fu; Hongjun Song; Lei Wang; Qinsheng Wei; Ping Sun; Lin Liu; Xuelei Zhang (Acta Oceanologica Sinica, 2018)

A New Approach of Rpf Addition to Explore Bacterial Consortium for Enhanced Phenol Degradation Under High Salinity Conditions - Ziqiao Li; Yunge Zhang; Yuyang Wang; Rongwu Mei; Yu Zhang; Muhammad Zaffar Hashmi; Hongjun Lin; Xiaomei Su (Current Microbiology, 2018)

Development and Application of Urban High Temporal-Spatial Resolution Vehicle Emission Inventory Model and Decision Support System - Yi Zhang; Lin Wu; Chao Zou; Boyu Jing; Xiaoyu Li; Tim Barlow; Turpin Kevin; Michel André; Yao Liu; Peipei Ren; Gongdong Wang; Hongjun Mao (Environmental Modeling & Assessment, 2017)

Breeding potential of maize germplasm populations to improve yield and predominant heterotic pattern in Northeast China - Hongjun Yong; Zhenguo Jin; Li Gao; Lin Zhang; Xianjun Liu; Fangjun Zhang; Xiaocong Zhang; Degui Zhang; Mingshun Li; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Heterosis and combining ability of seven maize germplasm populations - Xiaocong Zhang; Hongjun Yong; Zhiqiang Zhou; Chaoshu Zhang; Ming Lu; Qi Sun; Lin Zhang; Mingshun Li; Degui Zhang; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

The use of chlorogenic acid and its analogues as inhibitors: an investigation of the inhibition of sortase A of Staphylococcus aureus using molecular docking and dynamic simulation - Chongwei Bi; Lin Wang; Xiaodi Niu; Hongjun Cai; Xiaobo Zhong; Xuming Deng; Tiedong Wang; Dacheng Wang (Biotechnology Letters, 2016)

Numerical Model-Based Artificial Neural Network Model and Its Application for Quantifying Impact Factors of Urban Air Quality - Jianjun He; Ye Yu; Yaochen Xie; Hongjun Mao; Lin Wu; Na Liu; Suping Zhao (Water, Air, & Soil Pollution, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Trade-off between seed defensive traits and impacts on interaction patterns between seeds and rodents in forest ecosystems - Zhibin Zhang; Zhenyu Wang; Gang Chang; Xianfeng Yi; Jiqi Lu; Zhishu Xiao; Hongmao Zhang; Lin Cao; Fusheng Wang; Hongjun Li; Chuan Yan (Plant Ecology, 2016)

Association of Serum Bisphenol-A Concentration and Male Reproductive Function Among Exposed Workers - Wanli Zhuang; Kusheng Wu; Yukai Wang; Hongjun Zhu; Zanzhang Deng; Lin Peng; Guanghui Zhu (Archives of Environmental Contamination and Toxicology, 2015)

The Alteration of MiR-222 and Its Target Genes in Nickel-Induced Tumor - Jing Zhang; Yang Zhou; Lin Ma; Shunquan Huang; Ruijin Wang; Rongrong Gao; Youjun Wu; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2013)

Isolation and Characterization of a Novel Noncoding RNA from Nickel-Induced Lung Cancer - Jing Zhang; Yang Zhou; Youjun Wu; Lin Ma; Yingying Fan; Xuan Kang; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2012)

Common variant (rs9939609) in the FTO gene is associated with metabolic syndrome - Donghao Zhou; Hongjun Liu; Ming’ai Zhou; Shengxiang Wang; Jingling Zhang; Lin Liao; Fang He (Molecular Biology Reports, 2012)

Membrane Bioreactors for Industrial Wastewater Treatment: A Critical Review - Hongjun Lin; Weijue Gao; Fangang Meng; Bao-Qiang Liao; Kam-Tin Leung; Leihong Zhao; Jianrong Chen; Huachang Hong (Critical Reviews in Environmental Science and Technology, 2012)

The expression of Na, K-ATPase in Litopenaeus vannamei under salinity stress - Hongyan Sun; Lvping Zhang; Chunhua Ren; Chang Chen; Sigang Fan; Jian Jun Xia; Hongjun Lin; Chaoqun Hu (Marine Biology Research, 2011)